2020
DOI: 10.1002/adfm.201910504
|View full text |Cite
|
Sign up to set email alerts
|

MXene Composite and Coaxial Fibers with High Stretchability and Conductivity for Wearable Strain Sensing Textiles

Abstract: The integration of nanomaterials with high conductivity into stretchable polymer fibers can achieve novel functionalities such as sensing physical deformations. With a metallic conductivity that exceeds other solution‐processed nanomaterials, 2D titanium carbide MXene is an attractive material to produce conducting and stretchable fibers. Here, a scalable wet‐spinning technique is used to produce Ti3C2Tx MXene/polyurethane (PU) composite fibers that show both conductivity and high stretchability. The conductiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
301
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 373 publications
(319 citation statements)
references
References 50 publications
(141 reference statements)
1
301
1
Order By: Relevance
“…[35,48] However, in terms of electrical conductivity, it has been shown that MXene films prepared from aqueous dispersions have significantly higher conductivity than those prepared from DMF and DMSO. [41] Depending on the application, the solvent should be carefully selected with stability and electronic properties in mind. From the results of these works, we have a "library" of polar organic solvents to choose from that can disperse MXene, opening new avenues to develop a wide range of MXene composite dispersions for fiber spinning and other processing methods.…”
Section: Solvent Selection and Stabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…[35,48] However, in terms of electrical conductivity, it has been shown that MXene films prepared from aqueous dispersions have significantly higher conductivity than those prepared from DMF and DMSO. [41] Depending on the application, the solvent should be carefully selected with stability and electronic properties in mind. From the results of these works, we have a "library" of polar organic solvents to choose from that can disperse MXene, opening new avenues to develop a wide range of MXene composite dispersions for fiber spinning and other processing methods.…”
Section: Solvent Selection and Stabilitymentioning
confidence: 99%
“…Due to the good dispersibility of MXene in polar solvents, a large range of materials, e.g., PCL, [36] polyurethane (PU), [41] PEDOT:PSS ( Figure 3c-ii,iii), [99] and GO, [111,112] have been added as components to the spinning dope to produce MXene-based composite fibers. These spinnable materials significantly improved the processability of MXene flakes into fibers.…”
Section: Wet Spinningmentioning
confidence: 99%
See 1 more Smart Citation
“…MXenes were discovered in 2011 by Gogotsi and coworkers. (2,3,(6)(7)(8)(9)(10) MXenes are typically synthesized from the parent MAX phases (M n+1 AX n with early transition metals (group 13-16 elements), carbon, and nitrogen, with n = 1-4) by strong acid etching the layer obtained by intercalation-assisted delamination. MXene (M n+1 X n T x ) flakes with a high aspect ratio (up to ≈106) and abundant terminating functional groups (T x ) are desirable for producing polymer composites with novel functionalities.…”
Section: Introductionmentioning
confidence: 99%
“…MXene (M n+1 X n T x ) flakes with a high aspect ratio (up to ≈106) and abundant terminating functional groups (T x ) are desirable for producing polymer composites with novel functionalities. (9) More than 60 distinct types of pure MAX phases and 20 types of MXenes have been discovered. (11) MXenes have been employed in energy storage, (1,(10)(11)(12)(13)(14)(15)(16)(17) catalysis, (3,(10)(11)(12)16) supercapacitors, (10,13,17,18) Li-ion batteries, (10,13,14,19) electronic devices, (1,20) sensing, (2,(11)(12)(13)(15)(16)(17)(20)(21)(22) biomedical applications, (10,14,15,19,(23)(24)(25) and environmental remediation.…”
Section: Introductionmentioning
confidence: 99%